2012
DOI: 10.1152/japplphysiol.01031.2011
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise training improves age-related declines in leg vascular conductance and rejuvenates acute leg blood flow responses to feeding and exercise

Abstract: I, Rennie MJ. Resistance exercise training improves age-related declines in leg vascular conductance and rejuvenates acute leg blood flow responses to feeding and exercise. J Appl Physiol 112: 347-353, 2012. First published October 13, 2011 doi:10.1152/japplphysiol.01031.2011.-One manifestation of age-related declines in vascular function is reduced peripheral (limb) blood flow and vascular conduction at rest and in response to vasodilatory stimuli such as exercise and feeding. Since, even in older age, resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 37 publications
9
67
0
1
Order By: Relevance
“…Under these conditions, and in agreement with the work of Vincent et al, who provided mixed macronutrition (44), we were able to detect increases in both muscle MBV and LBF (26), which, although these increases did not correlate, suggests that expansion of the endothelial surface is an important physiological response to feeding. Of the signals regulating this response, both increased availability of insulin and L-arginine (the precursor for NO synthesis) have been shown to regulate muscle perfusion via NO-dependent vasodilation of precapillary arterioles (42).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Under these conditions, and in agreement with the work of Vincent et al, who provided mixed macronutrition (44), we were able to detect increases in both muscle MBV and LBF (26), which, although these increases did not correlate, suggests that expansion of the endothelial surface is an important physiological response to feeding. Of the signals regulating this response, both increased availability of insulin and L-arginine (the precursor for NO synthesis) have been shown to regulate muscle perfusion via NO-dependent vasodilation of precapillary arterioles (42).…”
Section: Discussionsupporting
confidence: 92%
“…Whereas the optimal nutritive network consists of tortuous capillaries contacting myocytes, the nonnutritive network supplies muscle connective tissue and adipocytes and has minimal myocyte contact (33,45). Whereas feeding has been shown to stimulate both limb (i.e., femoral and brachial) (26,28,34) and muscle nutritive (30,33) blood flow, relationships between muscle AA utilization and blood flow remain poorly defined. Nonetheless, evidence is mounting that recruitment of muscle microvasculature is important in maintaining protein (40) and carbohydrate (CHO) (42,43) …”
mentioning
confidence: 99%
“…In addition to this, we observed no significant vascular response to feeding and no evidence of capillary recruitment or increased leg blood flow. This supports previous demonstrations of diminished vascular responsiveness to feeding with age, which may contribute to a blunted anabolic response with aging (35,44,47). Finally, although we have demonstrated a significant persistence of elevated MPS with pulse but not bolus feeding, net anabolism over the 4-h postprandial period was only 6% greater and not significantly different.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly in these individuals we found that methacholine, as expected, was able to increase macro-and microvascular responses to mixed macronutrient (I.V) "feeding", but that this was not associated with improved MPS responses . We rationalised that this lack of association may be due to already optimal vascular and muscle protein synthetic responses to nutrition in the young that are not apparent in older individuals Phillips et al 2012). In addition, we considered the difficulties in applicability of a pharmacological agent as a health-based intervention tool and instead moved towards using cocoa flavanols, a neutraceutical agent that has already been shown to be well tolerated (Balzer et al 2008) and effective at improving vascular function in a wide variety of healthy and disease-based cohorts (Heiss et al 2010).…”
Section: Discussionmentioning
confidence: 99%